1996
DOI: 10.1073/pnas.93.13.6399
|View full text |Cite
|
Sign up to set email alerts
|

31P NMR magnetization transfer study of the control of ATP turnover in Saccharomyces cerevisiae.

Abstract: ABSTRACT31P NMR magnetization transfer measurements have been used to measure the steady state flux between P1 and ATP in yeast cells genetically modified to overexpress an adenine nucleotide translocase isoform. An increase in Pi -> ATP flux and apparent ratio of moles of ATP synthesized/ atoms of oxygen consumed (P:O ratio), when these cells were incubated with glucose, demonstrated that the reactions catalyzed by the translocase and F1Fo ATP synthase were readily reversible in vivo. However, when the same c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Up to this point, it has been assumed that the mitochondrial F 1 F 0 -ATP synthase flux, which constitutes only a small part of the total V ATP measured, is unidirectional. However, it has been shown that at low rates of respiration (e.g., resting muscle) the F 1 F 0 -ATP synthase reaction is near to equilibrium and that mitochondrial exchange between P i and ATP can make a significant contribution to the measured V ATP (50). Taken together, if there would have been an effect of DPI on the rate of net resting mitochondrial ATP production, this effect might not be measurable due to the large contribution of glycolytic exchange flux and possibly also a significant contribution of mitochondrial exchange flux to the total measured V ATP .…”
Section: Discussionmentioning
confidence: 99%
“…Up to this point, it has been assumed that the mitochondrial F 1 F 0 -ATP synthase flux, which constitutes only a small part of the total V ATP measured, is unidirectional. However, it has been shown that at low rates of respiration (e.g., resting muscle) the F 1 F 0 -ATP synthase reaction is near to equilibrium and that mitochondrial exchange between P i and ATP can make a significant contribution to the measured V ATP (50). Taken together, if there would have been an effect of DPI on the rate of net resting mitochondrial ATP production, this effect might not be measurable due to the large contribution of glycolytic exchange flux and possibly also a significant contribution of mitochondrial exchange flux to the total measured V ATP .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence from yeast that glycolytic reactions contribute strongly to fATP measured by 31 P-magnetic resonance spectroscopy (32,33), indicating that reversible glycolytic reactions might explain the higher ATP synthetic rates. Finally, mitochondrial ATP formation is not strictly irreversible (34). As a consequence, the apparent forward flux (fATP) exceeds the net production many times (26).…”
Section: Different Mrs Parameters Of Skeletal Muscle Energy Metabolismmentioning
confidence: 99%
“…18,19 If the substrate remains the same, a drop in PaO ratio below the theoretical or control value is caused by diversion of the proton¯ux into the leak pathway.…”
Section: Measurement Of Proton Conductancementioning
confidence: 99%